“Good Governance & Integrity in the Digital Industrial Revolution Era” - UMP, PNC (2019)
In the efforts to enhance knowledge and boost the effectiveness of good governance and integrity in the era of Industrial Revolution 4.0 (IR4.0), the Faculty of Industry Management’s (FIM) Governance & Integrity Centre (FGIC) at Universiti Malaysia Pahang (UMP) recently collaborated with the State of Pahang Foundation (YP) to organize the FGIC 2019 annual conference at the Main Hall of YP Complex in Tanjung Lumpur, Kuantan. Running for two days, from August 19 to 20, 2019, the FGIC 2019 annual conference also received the support of related federal government agency, Integrity Institute of Malaysia (IIM).